Drinking in the dark: shedding light on young people’s alcohol consumption experiences - Wilkinson, Samantha (Taylor & Francis online, 2016)
This paper draws on 12 months of ethnographic research to explore the drinking experiences of young people, aged 15-24, living in the suburban case study locations of Chorlton and Wythenshawe, Manchester, UK. This paper moves beyond the contemporary geographical imaginary of alcohol consumption as a city-centre issue, to explore suburban indoor and outdoor drinking cultures. Through paying attention to atmospheres of darkness and lightness, I show how drinkscapes are active constituents of young people’s drinking occasions, rather than passive backdrops. More than this, I illustrate how young people transform dark and light drinkscapes, thereby shaping the drinking practices of themselves and others. Through looking at the interplay between the curating of an atmosphere, and the experience of that atmosphere when bodies, and practices are inserted into it, this paper offers a different take on the ‘drinking at home is bad, drinking in public spaces is good’ argument, with original policy suggestions.